E-Marketing for Customer Relationship Management in Banking Services (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study pursues to stretch an overall interpretation on Electronic Marketing on the Customer Relationship Management. The banking industry is extremely information-intensive, and thus makes it important to recognize new development in strategy to create value through the e-commerce on E-Marketing. Electronic Marketing emerges from the Internet and web technology to facilitate of internet and its associated technologies. It focuses on internet- or web-based interaction with their customers. E-marketing enables service sectors to provide appropriate services and products to satisfy the customers so as to retain customer royalty and enhance customer profitability. Electronic Marketing is evolved recently with the emergence of information technology such as Internet and web technologies for more customer satisfaction.In contemporary epoch E-marketing is an innovative marketing apparatus in globalized economy. In present scenario information technology, integration of knowledge, internet and healthy relationships with customers the crucial assets for the survival of E-marketing in the globalize economy. In this paper, we define impact of E-marketing with the customer relationship management. Electronic Marketing is evolved recently with the emergence of information technology such as Internet and web technologies in private sectors Banks for more customer satisfaction. In this paper, a theoretical impetus from new technologies in banking services such as mobile banking, internet banking etc is discussed to bring technology – led marketing process towards optimizing profit. This paper also brings out benefits of e-marketing from the point of view of banks, their technology and customer values.